Construction of a prognostic prediction model in liver cancer based on genes involved in integrin cell surface interactions pathway by multi-omics screening - Yu, Xiang; Zhang, Hao; Li, Jinze; Gu, Lu; Cao, Lei; Gong, Jun; Xie, Ping; Xu, Jian (Frontiers in Cell and Developmental Biology, 2024)
Background: Liver cancer is a common malignant tumor with an increasing incidence in recent years. We aimed to develop a model that canby integrate integrating clinical information and multiomics profiles of genes to predict survival of patients with liver cancer.The multi-omics data were integrated to identify liver cancer survival-associated signal pathways. Then, a prognostic risk score model was established based on key genes in a specific pathway, followed by the analysis of the relationship between the risk score and clinical features as well as molecular and immunologic characterization and immunology of the key genes included in the prediction model. The function experiments was were performed to further elucidate the undergoing molecular mechanism.Results: Totally, 4 pathways associated with liver cancer patients' survival were identified. In the pathway of integrin cell surface interactions, low expression of COMP and SPP1, and few low CNVs level of COL4A2 and ITGAV was were significantly related to prognosis. Based on above 4 genes, the risk score model for prognosis was established. Risk score, ITGAV and SPP1 were the most significantly positively related to activated dendritic cell. COL4A2 and COMP were the most significantly positively associated with Type 1 T helper cell and regulatory T cell, respectively. The Nnomogram (involved T staging stage and risk score) may better predict short-term survival. In vitro mechanism studyThe cell assay showed that overexpression of ITGAV promoted tumorigenesis.The risk score model constructed with four genes (COMP, SPP1, COL4A2 and ITGAV) may be used to predict survival in liver cancer patients.